Prediksi Klasifikasi jumlah Pembaca Sebuah Artikel pada Jurnal Biram Samtani Dengan Metode Bayesian Classification - S, Richasanty Septima; Zulfa, Ira; Gemasih, Husna; Saputra, Mahmuda; Israk, Al (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
One of the open access Open Journal System (OJS)-based reading media is the Biramsamtani Journal, which is the official publication media of scientific articles published by the journal manager, namely the Institute for Research and Community Service of Gajah Putih University, Central Aceh, Indonesia. Until now, the number of scientific articles that have been published is 76 articles with a total of 26,938 viewers read in 10 editions, 7 volumes, and for 5 years of publication. In the Biram Samtani Journal, an uneven and erratic number of readers was found. Where the causative factors that cannot be determined are due to too many abstracts, the position of the article in the published edition or the category of the article that needs to be adjusted to the month of publication. This problem will be studied using data mining by analyzing data using Bayesian Classification. From the test results obtained to predict the number of readers, the best obtained is model 2 with the composition of training data and 80:20 test data with an accuracy of 79.92%, accuracy of 80.15% and recall of 72.36% while for the classification of the number of readers in Biramsamtani journal articles based on the probability value of 47.7% (Low), 30.76% (High), and 21.53% (Medium).